Community Practice: Strengthening Primary Health Care with Nursing Students - Luz Enith Velásquez Restrepo,; Doris León Mejía,; Yaneth Esperanza Jaramillo Sánchez,; Lina Marcela Suárez Gaviria,; Diana María Galvis Gómez, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Primary Health Care (PHC) is essential to guarantee universal access and equity in health. The incorporation of nursing students in community practices emerges as a promising strategy to strengthen PHC, while enriching the training of future professionals. This article explores the impact and benefits of community practice of nursing students in the context of PHC, highlighting its potential to address the health needs of communities and develop essential competencies in students. Community practice is an essential component in the training of nursing students, allowing the development of clinical, educational and social competencies in real scenarios. This study analyzes the impact of student participation in Primary Health Care (PHC) activities in vulnerable communities, highlighting how this experience strengthens both their professional training and community health. Through a qualitative-descriptive methodology, data were collected through observations, semi-structured interviews and field diaries. The results show improvements in health promotion, community education and the link between the health system and the population. It is concluded that community practice is a key tool to reinforce the comprehensive approach to PHC and train professionals committed to social welfare. Integrating nursing students into community practice not only improves their skills and knowledge, but also strengthens primary care. This article explores how the active participation of nursing students in community settings can improve both their training and the quality of primary health care.